2015
DOI: 10.1186/s13037-015-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and surgical outcomes: a systematic review

Abstract: The importance of vitamin D for musculoskeletal health has long been recognized, and awareness of significant extra-skeletal effects in health and disease is rapidly emerging. Although it has been possible for many decades to quantify serum markers of vitamin D deficiency, and to correct deficiency at low cost and with high safety, the influence of vitamin D status on post-surgical outcomes has only recently been identified as a research topic of interest. To the present, these data have not been the subject m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 55 publications
1
40
0
5
Order By: Relevance
“…Correlations between vitamin D deficiency and a variety of clinical conditions have been reported in numerous studies [1112131415161718]. Vitamin D deficiency is defined as total 25(OH)D concentration less than 20 ng/mL, regardless of its bioavailability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations between vitamin D deficiency and a variety of clinical conditions have been reported in numerous studies [1112131415161718]. Vitamin D deficiency is defined as total 25(OH)D concentration less than 20 ng/mL, regardless of its bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that vitamin D deficiency correlates with various clinical conditions and parameters, including osteoporosis, cardiovascular diseases, autoimmune diseases, schizophrenia, surgical outcomes, and cancer risk [1213141516171819]. Nonetheless, the causality is still unproven.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies which have linked hypovitaminosis D to adverse post-surgical outcomes following a wide range of procedures [14]. Iglar and Hogan reviewed 31 studies linking hypovitaminosis D to complications such as increased risk of graft failure in renal patients [15], wound breakdown and infection [16,17], and organ transplant rejection [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Аналіз сучасних даних про вплив статусу цього вітаміну на постхірур-гічні результати, дозволив Iglar P. J. et.al. [9] зробити висновок про те, що гіповітаміноз D пов'язаний з несприятливими результатами після різноманітних операцій.…”
Section: короткий аналіз сучасного стану дослі-джень по вивченню ефекunclassified